Analisa Lembaran Komposit berpenguat Serbuk Ijuk mesh 60 Menggunakan Matrik Karet Terhadap Radiasi Sinar Gamma Dengan variasi Komposisi Serbuk Ijuk 0 Phr, 15 Phr, 25 Phr - Prasetyo, Hari, Masyrukan, ST, MT, Ir. Bibit Sugito, MT (2016)
The purpose of this study was to utilize renewable lalam hasi as a substitute for metal materials. It is also to determine the absorption of gamma-ray radiation of the powder berpenguat composite fibers are fibers powder can absorb gamma radiation. Composite manufacturing process begins with the preparation of materials to be used, namely: powder fibers, latex I radiation with a concentration of 60%, and chemicals (ionol, ZnO, darvan, sulfur, ZDEC). Pollination fibers by way mengiling, mashing and blending the fibers during 1 month and penggemesan powder with a mesh fibers 60. Furthermore, the process of dispersion by means of chemicals mixed in a dispersion tube with a predetermined composition for 24 hours. After the mixing of composite materials by means berlahan stirred for 15 minutes. After the composite materials that have been mixed is poured into a mold that has been determined. The test specimens do is Pengujan gamma with standard ISO 18-6478 - 2000, and the journal Kristiyanti, BATAN Nuclear Device Engineering Center (2011) with a variety of powder composition fibers 0 phr, 15 phr, 25 phr. The test results can be concluded very highest absorption in the composite powder composition fibers 25 phr, ie 40.15% absorption rate and absorption of the smallest on the composition 0 phr, ie 29.66% absorption rate. Keywords: Powder Ijuk Aren, Latex, Chemicals, Sheet Composite